Training and well-equipped facility increases the odds of skills of health professionals on helping babies breathe in public hospitals of Southern Ethiopia: cross-sectional study - Abera Mersha; Shitaye Shibiru; Teklemariam Gultie; Nega Degefa; Agegnehu Bante (BMC, 2019)
Abstract Background Health professionals equipped with the adequate skills of helping baby breath remain the backbone in the health system in improving neonatal outcomes. However, there is a great controversy between studies to show the proximate factors of the skills of health care providers in helping babies breathe. In Ethiopia, there is a paucity of evidence on the current status of health care provider's skills of helping babies breathe despite the improvement in neonatal health care services. Therefore, this study intends to fill those gaps in assessing the skills of helping babies breathe and its associated factors among health professionals in public hospitals in Southern Ethiopia. Methods A facility-based cross-sectional study was conducted among 441 health professionals from March 10 to 30, 2019. A simple random sampling method was used to select the study participants. The data were collected through pre-tested interviewer-administered questionnaire and observational checklist. A binary logistic regression model was used to identify significant factors for the skills of helping babies breathe by using SPSS version 25. The P-value < 0.05 used to declare statistical significance. Results Overall, 71.1% (95%CI: 66.2, 75.4%) of health professionals had good skills in helping babies breathe. Age group from 25 to 34 (AOR = 2.24; 95%CI: 1.04, 4.81), training on helping babies breathe (AOR = 2.69; 95%CI: 1.49, 4.87), well-equipped facility (AOR = 2.15; 95%CI: 1.09, 4.25), and adequate knowledge on helping babies breathe (AOR = 2.21; 95%CI: 1.25, 3.89) were significantly associated with a health professionals good skill on helping babies breathe. Conclusions Even though a significant number of care providers had good skills in helping babies breathe, yet there is a need to further improve the skills of the provider in helping babies breathe. Hence, health facilities should be equipped with adequate materials and facilitate frequent training to the provider.